Xri: A study of contact, and phonetic and phonological change - Mössmer, Martin (Linguistics, 2022)
Xri is a Khoekhoe language spoken among the Griekwa people of the Northern Cape, South Africa, and was thought until recently to be extinct. Fieldwork conducted in 2018 and 2019 documented Xri spoken by 27 semi-speakers and rememberers, the last speakers of this dying language. The absence of satisfactory studies of the phonetic and phonological effects of language obsolescence and death in African languages, particularly the endangered Indigenous Click Languages, necessitates further investigation. I describe the phonetic and phonological effects on Xri of language contact with Afrikaans over 170 years and critique previous studies of Xri. Innovative data collection techniques used to obtain the data are detailed. Xri phonemes not found in Afrikaans are more likely to undergo change, and the production of key classes of phonemes—such as nasal vowels—are characteristic of informants with high spoken Xri proficiency. The distinctions between click types are unstable in the speech of most informants but there is minimal loss of click realisation, and click accompaniments are resistant to change. A metric developed for measuring speaker competency is also demonstrated. Informants' spoken Xri competency is measured based on their syntactic, morphological, phonetic, and tonological performance (50%), as well as overall lexicon size (50%). Informants are divided into three group case studies by competency score, which are shown to correspond to the degree of change in their realisation of Xri phonetic features. Click sounds have persisted in the speech of even informants with low Xri proficiency, and the findings support the hypothesised salience of clicks as a phonological class. The accompaniments of click phonemes, however, displayed greater resilience to change than the click phones themselves. The contextual biographical data obtained support the linguistic assessment of the estimated date of Xri moribundity by 1960. The metric developed to measure speaker competency has—with further testing—the potential to contribute to future research in critically endangered language research. The data collection methods used for this study are also recommended for future research in situations of language death.